Healthcare professionals and the practice of the human rights of individuals with mental disorders - Carla Aparecida Arena Ventura; Viviana Carolina Oyan de Moraes; Márjore Serena Jorge (Universidade Federal de Goias, 2013)
This qualitative study aimed at describing the perception that healthcare professionals of a Psychosocial Care Center (CAPS, as per its acronym in Portuguese) make of the human rights of individuals with mental health disorders and the means used to make rights effective in health care. Data were collected in 2010 by semi-structured interviews with seven professionals, and submitted to content analysis. It was observed that subjects have different perceptions regarding the human rights of individuals with mental health disorders, centered on freedom, protection of life, living in society and being a participative citizen. Despite the political advancements, gaps still hinder making the rights of people with mental disorders effective, which could be supplied by an engagement of the family, society, and government. Healthcare professionals have played an important role as of regarding rights, helping to raise awareness of patients and their families, aiming at their social reinsertion. Descriptors: Human Rights; Right to Health; Mentally Ill Persons; Mental Health.